2019
DOI: 10.3390/medicina55070387
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of and Attitude towards Traditional and Complementary Medicine among Ebola Survivors in Sierra Leone

Abstract: Background and objectives: In addition to conventional healthcare, Ebola survivors are known to seek traditional and complementary healthcare (T&CM) options to meet their healthcare needs. However, little is known about the general beliefs of Ebola survivors regarding T&CM and the impact of these beliefs in influencing their decisions around T&CM use. This study examines Ebola survivors’ attitudes towards T&CM use in Sierra Leone. Materials and Methods: We conducted a nationwide quantitative cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
(72 reference statements)
0
5
0
1
Order By: Relevance
“…Most studies on stigma among EVD survivors have focussed on its magnitude and nature both immediately following and over a number of years after discharge from an Ebola treatment centre [11-13, 17-21, 23, 25, 40]. Although recent studies have reported the use of informal healthcare services among EVD survivors [41,42], globally, no study to date has reported whether EVD-related stigma is associated with T&CM utilisation among EVD survivors. In addition, none of the published studies in Sierra Leone on EVD survivors has explored the sociodemographic and health-related factors associated with EVDrelated stigma.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on stigma among EVD survivors have focussed on its magnitude and nature both immediately following and over a number of years after discharge from an Ebola treatment centre [11-13, 17-21, 23, 25, 40]. Although recent studies have reported the use of informal healthcare services among EVD survivors [41,42], globally, no study to date has reported whether EVD-related stigma is associated with T&CM utilisation among EVD survivors. In addition, none of the published studies in Sierra Leone on EVD survivors has explored the sociodemographic and health-related factors associated with EVDrelated stigma.…”
Section: Introductionmentioning
confidence: 99%
“…Personal and health system factors, including the negative attitudes of healthcare providers towards survivors, were cited as reasons why Ebola survivors decided to seek T&CM. These Sierra Leonean studies also found that disclosure of T&CM use among Ebola survivors was low, which is an indication that communication about T&CM use between healthcare providers and Ebola survivors is not optimal [19][20][21][22]. With these issues and circumstances in mind, we wanted to understand in this study how healthcare providers interact with Ebola survivors regarding T&CM.…”
Section: Introductionmentioning
confidence: 99%
“…Joint pain and abdominal pain were the most common post-Ebola indications for T&CM use [19]. Ebola survivors were attracted to using T&CM because of personal beliefs, economic, psychological, social and cultural needs as well as health system factors [19][20][21][22]. These factors include the ineffectiveness of conventional medicine, healthcare providers' negative attitudes toward Ebola survivors, high cost of, and unavailability of conventional medicine to manage post-Ebola symptoms and T&CM being in line with Ebola survivors' culture and tradition [19,21,22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations